Revisiting the determinants of knowledge-sharing behavior in organizations: a meta-analytic structural equation model application - Zaremohzzabieh, Zeinab; Mohd Rasdi, Roziah (Emerald Publishing Limited, 2023)
Purpose – The existing literature on knowledge-sharing (KS) behavior in the organizational context demonstrates that there is diversity, if not divergence, in understanding KS. Thus, this paper aims to integrate social cognitive theory and social exchange theory to construct a research model for determining the incentive for knowledge sharing among individuals in organizations based on past empirical results. Design/methodology/approach – Accordingly, the methodology adopted in this study is the meta-analytic structural equation modeling based on the data gathered from 78 studies (80 samples, n = 29,318). Findings – The most significant predictors of KSB were organizational support and social interaction ties, whereby KS intention and attitude were most optimally predicted by organizational commitment, knowledge self-efficacy, social interaction ties, organizational expectancy and reciprocal benefit. This study carried out a moderation analysis to look into potential causes of inconsistent results. Originality/value – This meta-analysis shows the most influencing factors that trigger KSB in organizations. Moreover, this study clarifies the possible reasons for the inconsistent findings of the previous studies. Thus, it contributes to the KS literature.